Relações intergovernamentais e uso de sistemas de informação em políticas sociais no Brasil - Ribeiro, Manuella Maia (2017)
The aim is to identify and explain the adaptations made by local public managers in the use of information systems in social policies of the national level. One of the characteristics of the national level's social policies is the adoption of information systems that assist in the management of various stages of social policies, such as diagnosis, monitoring and evaluation. Sometimes these systems are shared with other levels of government, especially local governments. In order to understand the local adaptations, the focus of this research was the information systems users within local governments. The assumption adopted was that the users of these systems in the local level can modify the context of use of technology and not only the technology or the information system itself in order to meet what was defined by the national instance, i. e., users create adaptations according to local specificities in order to keep the system running. Furthermore, the adaptations can be diverse according to the local context in which the information systems are used. Therefore, in order to understand how local adaptations occur in the implementation of information systems in national level social policies, a case study was carried out about the Single Registry of Social Programs of the Brazilian Federal Government (Cadastro Único), an information system built to collect data of low-income population in Brazil. This low-income population database is used for national social policy implementation. The registrations made in this system are under the responsibility of the 5,570 Brazilian local governments, including the inclusion, alteration or exclusion of registered people. The research data collection was based on: a) document analysis of legislation, manuals, official documents, among others; b) online research with local level managers of Cadastro Único; and, c) semi-structured interviews with national and local level public managers related to the Cadastro Único. Data analysis was based on the comparison between the norms defined by the national level and the effective implementation of the system by the users in the local governments, allowing to identify and to categorize the local adaptations. The research analysis pointed out that the information systems in decentralized social policies in Brazil are generally characterized by centralization. The national level defines its objectives, norms and forms of implementation and the local governments only execute information systems actions according to the rules defined by the national authority. However, the analysis also showed that this centralization does not prevent local governments to make adaptations in the use of these systems both to meet the objectives of the national government and to use the data in their local policies. The adaptations were also categorized according to four user profiles and local adaptations in the use of information systems in national level social policies: I) Little Adaptive; II) Adaptive Control; III) Adaptive Use; and, IV) Fully Adaptive. This ability of the local user to modify the implementation of information systems in decentralized social policies generated a concept named here as adaptive level bureaucrat. This concept highlights the inevitability of adaptations of information systems at the local level.